Overexpression of human epidermal growth factor receptor 2 protein in urothelial carcinoma of the urinary bladder in Ibadan: a single-institutional experience (2020)
Background: Overexpression of human epidermal growth factor receptor 2 (HER 2) protein has been shown to have both prognostic and therapeutic values in several malignancies including urothelial carcinoma of urinary bladder (UCB). Aims: This study aimed to determine HER 2 protein overexpression and evaluate its correlation with clinico pathological parameters in UCB. Materials and Methods: This was a descriptive-analytical study involving the immunohistochemical review of all histologically diagnosed urinary bladder malignancy in the Department of Pathology, University College Hospital, Ibadan, between January 2002 and December 2016. Urinary bladder malignancies whose tissue blocks could not be found and/or demographic data were not available were excluded. Immunohistochemistry analysis was done using rabbit anti HER 2 antibody (Biocare) and American Society of Clinical Oncology/College of American Pathologists guidelines established for breast cancer were used for HER 2 status scoring. The statistical analysis was carried out usingthe Statistical Package for the Social Sciences, version 22 (SPSS Inc, Chicago, Illinois, USA). Results: HER 2 overexpression was found in four (6.3%) cases. All the HER 2 positive cases were males. One (2.9%) of the 35 high grade UCB showed positive HER 2 overexpression, whereas three (10.7%) of the 28 low grade tumor were positive for HER 2 protein overexpression.There was no statistically significant association between HER 2 protein overexpression and histological grades of UCB and muscle invasion by the tumor. Conclusion: Our study demonstrated the low percentage of HER 2 overexpression in UCB with no significant association with tumor grades and muscle invasion. Larger samples involving multiple centers can provide more robust information and further evaluate HER 2 overexpression in urothelial carcinoma in our environment.